Respuesta :

Answer:

a)

[tex] h^{-1}(x) = 2x + 8 [/tex]

b)

[tex] k^{-1}(x) = \pm\sqrt{x - 3} [/tex]

Step-by-step explanation:

To find an inverse function, follow these steps.

Step 1. Write the function.

Step 2. Replace the function name in function notation with y.

Step 3. Switch x and y.

Step 4. Solve for y.

Step 5. Replace y with function notation for inverse function.

Now let's do part a) following the steps above.

Step 1.

[tex] h(x) = \dfrac{1}{2}x - 4 [/tex]

Step 2.

[tex] y = \dfrac{1}{2}x - 4 [/tex]

Step 3.

[tex] x = \dfrac{1}{2}y - 4 [/tex]

Step 4.

[tex] x = \dfrac{1}{2}y - 4 [/tex]

[tex] x + 4 = \dfrac{1}{2}y [/tex]

[tex] 2x + 8 = y [/tex]

[tex] y = 2x + 8 [/tex]

Step 5.

[tex] h^{-1}(x) = 2x + 8 [/tex]

Now let's do part b) following the steps above.

Step 1.

[tex] k(x) = x^2 + 3 [/tex]

Step 2.

[tex] y = x^2 + 3 [/tex]

Step 3.

[tex] x = y^2 + 3 [/tex]

Step 4.

[tex] x = y^2 + 3 [/tex]

[tex] x - 3 = y^2 [/tex]

[tex] y^2 = x - 3 [/tex]

[tex] y = \pm\sqrt{x - 3} [/tex]

Step 5.

[tex] k^{-1}(x) = \pm\sqrt{x - 3} [/tex]

ACCESS MORE